2021
DOI: 10.1186/s12893-021-01294-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, pattern and management outcome of intestinal obstruction among non-traumatic acute abdomen surgical admissions in Arba Minch General Hospital, Southern Ethiopia

Abstract: Background Intestinal obstruction is defined as a blockage or partial blockage of the passage of the intestinal contents. It is a potentially risky surgical emergency associated with high morbidity and mortality. Its pattern differs from country to country and even from place to place within a country. Therefore, this study aimed to find out the magnitude, pattern and management outcome of intestinal obstruction in Arba Minch General Hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…This study found that 116 (59.2%) of patients managed for bowel obstruction had favorable management outcome. Although this result is comparable to the result of the study in Turkey (58.1%) [ 22 ], it is lower than the findings of the study done in Nekemte specialized hospital 73.5% [ 10 ], Adama Hospital 75.4% [ 11 ], Asella hospital-75.7% [ 12 ], Arba Minch General Hospital-77.7% [ 13 ], Chiro Hospital-78.7% [ 14 ], Dilla Hospital-86.4% [ 15 ], University of Gondar Comprehensive Specialized Hospital-83.3% [ 16 ], Debre Birhan Referral Hospital-83.3% [ 5 ], 82% in south Wollo Zone Hospitals [ 17 ], 77% in Wolayita [ 18 ], Kenya-86.4% [ 28 ], and India-74% [ 29 ]. The possible reason for the observed discrepancy might be due to the difference in the professionals involved in the surgical management, the difference in the study settings, study period, and population.…”
Section: Discussionsupporting
confidence: 53%
“…This study found that 116 (59.2%) of patients managed for bowel obstruction had favorable management outcome. Although this result is comparable to the result of the study in Turkey (58.1%) [ 22 ], it is lower than the findings of the study done in Nekemte specialized hospital 73.5% [ 10 ], Adama Hospital 75.4% [ 11 ], Asella hospital-75.7% [ 12 ], Arba Minch General Hospital-77.7% [ 13 ], Chiro Hospital-78.7% [ 14 ], Dilla Hospital-86.4% [ 15 ], University of Gondar Comprehensive Specialized Hospital-83.3% [ 16 ], Debre Birhan Referral Hospital-83.3% [ 5 ], 82% in south Wollo Zone Hospitals [ 17 ], 77% in Wolayita [ 18 ], Kenya-86.4% [ 28 ], and India-74% [ 29 ]. The possible reason for the observed discrepancy might be due to the difference in the professionals involved in the surgical management, the difference in the study settings, study period, and population.…”
Section: Discussionsupporting
confidence: 53%
“…This study found that − 116 (59.2%) of patients managed for bowel obstruction had favorable management outcome. Although this result is comparable to the result of the study in Turkey (58.1%) [20], it is lower than the ndings of the study done in Nekemte specialized hospital-73.5% [10], Adama Hospital-75.4% [11], Asella hospital-75.7% [12], Adama Hospital-75.4% [11], Arba Minch General Hospital-77.7% [13], Chiro Hospital-78.7% [14], Dilla Hospital-86.4% [15], University of Gondar Comprehensive Specialized Hospital-83.3% [16], Debre Birhan Referral Hospital-83.3% [4], 82% in south Wollo Zone hospitals [17], 77% in Wolayita [18], Kenya-86.4% [26], and India-74% [27]. The possible reason for the observed discrepancy might be the difference in the way the management outcome was operationalized and measured, the difference in the professionals involved in the surgical management, the difference in the study settings, study period, and population.…”
Section: Discussioncontrasting
confidence: 44%
“…In our study, favorable management outcome was affected by gangrenous intraoperative nding. This is supported by the study conducted in Wolayita [18], Asella hospital [12], Arba Minch General Hospital [13], Chiro, Dilla, and Adama hospitals in which patients with viable small bowel volvulus and viable sigmoid volvulus were more likely to have favorable surgical management outcome compared to their counterparts [11,14,15].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[2][3][4][5][6][7] Bowel obstruction was found the second most common cause of non traumatic acute abdomen in this study which accounted 34.2% of all cases.This nding is in agreement with study done in NRH,TAH and Goba referral hospital.The most common cause of obstruction was found to be SBO and volvulus of small bowel(48.05% from total obstruction and 61.6% from SBO) was the leading cause of SBO.This is in contrast with study in addis abeba,Teklehaimanot general hospital ,Adama general hospital and certain African country study done from Nigeria by Adesunkami which all reported adhesion as frequent cause of SBO.Sigmoid volvulus was the most frequent cause of LBO in agreement with most studies in Ethiopia and other African countries. (1,7,(8)(9)(10)(11)(12)(13)18) …”
mentioning
confidence: 99%